2022
DOI: 10.3390/ijerph19031360
|View full text |Cite
|
Sign up to set email alerts
|

The Promise of Digital Self-Management: A Reflection about the Effects of Patient-Targeted e-Health Tools on Self-Management and Wellbeing

Abstract: Increasingly, people have direct access to e-Health resources such as health information on the Internet, personal health portals, and wearable self-management applications, which have the potential to reinforce the simultaneously growing focus on self-management and wellbeing. To examine these relationships, we searched using keywords self-management, patient-targeting e-Health tools, and health as wellbeing. Direct access to the health information on the Internet or diagnostic apps on a smartphone can help p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…The data should be easily understandable and practically applicable [ 65 ]. The health benefits of social media highlight the growing importance of this medium in people’s daily lives [ 66 , 67 ]. Nonetheless, as stated in a study of Zhang and partners [ 68 ], investigations are warranted on the veracity and security of health information found on social media.…”
Section: Discussionmentioning
confidence: 99%
“…The data should be easily understandable and practically applicable [ 65 ]. The health benefits of social media highlight the growing importance of this medium in people’s daily lives [ 66 , 67 ]. Nonetheless, as stated in a study of Zhang and partners [ 68 ], investigations are warranted on the veracity and security of health information found on social media.…”
Section: Discussionmentioning
confidence: 99%
“…The information should be simple, clear, and useful [62]. Social media is increasingly a factor in daily life and has shown a positive effect on health [63,64]. Nevertheless, the reliability and safety of the health information obtained on social media need evaluation [65].…”
Section: Relationship Between the Health Information Sources And Heal...mentioning
confidence: 99%
“…Among cancer patients, quality of life is a major outcome that can be improved by selfmanagement interventions, as demonstrated by Kim's metaanalysis [46]. However, a more recent meta-analysis showed that self-management interventions using digital means were only effective for improving self-efficacy and cancer-related fatigue but not quality of life [48]. These various findings may indicate that the link between self-management and well-being is not always straightforward [49].…”
Section: Discussionmentioning
confidence: 99%